CD4+CD8+ T follicular helper cells regulate humoral immunity in chronic inflammatory lesions - Murayama, Kosuke; Ikegami, Ippei; Kamekura, Ryuta; Sakamoto, Hiroshi; Yanagi, Masahiro; Kamiya, Shiori; Sato, Taiki; Sato, Akinori; Shigehara, Katsunori; Yamamoto, Motohisa; Takahashi, Hiroki; Takano, Ken-ichi; et al. (Frontiers in Immunology, 2022)
T follicular helper (Tfh) cells shape humoral immunity by facilitating B cell responses at initial and recall phases. Recent studies indicate possible involvement of Tfh cells in the process of chronic inflammation. However, the functional role of Tfh cells in persistent immune settings remains unclear. Here, we report CD4+CD8+ (double positive, DP; CD3+CD4+CD8+CXCR5hiPD-1hi) Tfh cells of germinal-center-type Tfh cells that abundantly resided in the fibroinflammatory lesions of immunoglobulin G4-related disease (IgG4-RD). Transcriptome analyses showed that DP-Tfh cells in the lesions of IgG4-RD preferentially expressed signature genes that identified cytotoxic CD8+ T cells, such as Eomes, CRTAM, GPR56, and granzymes in addition to CD70. Scatter diagram analyses to examine relationships between tissue-resident lymphocytes and various clinical parameters revealed that DP-Tfh cells were inversely correlated to the levels of serum IgG4 and local IgG4-expressing (IgG4+) memory B cells (CD19+CD27+IgD-) in IgG4-RD patients. Cell culture experiments using autologous tonsillar lymphocytes further suggested that DP-Tfh cells possessed a poor ability as B cell helpers and rather had a regulatory capacity for memory B cells. Considering that CD4+ (single positive, SP; CD3+CD4+CD8-CXCR5hiPD-1hi) Tfh cells differentiated into DP-Tfh cells under stimulation with survival factors IL-2 and IL-7 as assessed by in vitro experiments, these data imply that SP-Tfh cells are a possible origin of DP-Tfh cells under persistent inflammation. These findings illustrate a potential feedback loop for immune tolerance operated by such Tfh cells under chronic inflammatory conditions. Further studies of DP-Tfh cells may lead to a new modality to control unresolved humoral responses under pathological inflammation of IgG4-RD.